Efficacy of Shallots Infusion (Allium Cepa L.) as an Antidiarrhea in Mice (Mus Musculus) - Purohita, Adwisto Saktika; Aulia Andi Mustika; Lina Noviyanti Sutardi; Fadholly, Amaq (Faculty of Veterinary Medicine Universitas Brawijaya, 2022)
Shallots have been used for generations as traditional medicine, one of which is used in the treatment of diarrhea. This study determined the antidiarrheal activity of the shallot bulbs using intestinal protection and intestinal transit methods, and to determine the effective concentration that gives the best antidiarrheal effect in mice. This study used thirty mice and divided into six groups. The negative control group was given Tween 80 (1%), positive control group was given Loperamide HCl, and four various concentrations of shallot infusion treatment groups (1.25%, 2.5%, 5%, and 10 %). The treatment was given by the oral route. The parameters used in the intestinal protection method were frequency of defecation and feces consistency, while in intestinal transit method the parameters used were the percentage ratio of the marker trajectories compared to the overall length of the intestine. The results showed that the 1.25% concentration of shallot infusion indicated the best antidiarrheal activity and had a smaller ratio or stronger inhibition to intestinal peristaltic compared to all other concentrations, 2.5%, 5%, dan 10%. We concluded that shallot bulbs infusion with a concentration of 1.25% has the most effective anti-diarrheal effect. This research can be continued by measurement of other diarrheal parameters such as stool weight, as well as start and stop time of diarrhea to further clarify the anti-diarrheal potential of shallot bulb infusion.